RC beams damaged by cracking and strengthened with NSM CFRP/GFRP rods (Fracture and Structural Integrity, 2021)
The near surface mounted (NSM) method of inserting fiber reinforced polymer (FRP) elements (rods or lamina) into notches has been shown to be a good way for restoring reinforced concrete (RC) elements. The knowledge about the use of Glass-FRP rod following the NSM to reinforce RC beams is limited. This paper deals with the analysis of static and dynamic behaviour of RC beams with and without strengthening. The response of RC beams was assessed at different concrete’s damage level by non-destructive vibration tests. First, a couple of beams have been analysed: one RC beam subjected to bending and under vibration tests; another one beam, damaged by bending and strengthened with NSM Carbon-FRP rods tested again under vibration. Further, one RC beam damage was analysed under bending and vibration tests without strengthening; successively, the beam model with NSM GFRP rod has been tested following the same loading path. Below experimental results are shown and commented; in particular, changes in frequency values are related to the evolution of damage level affected RC beams with NSM CFRP and GFRP rods.
Keywords: NSM; CFRP/GFRP; Damage; Bending and Vibration tests; Frequency